STUDIES ON THE NUMEROUS MEDICINAL UTILITIES OF THE PLANT URGINEA INDICA: A COMPREHENSIVE OVERVIEW - NATH, JUNMONI (International Journal of Current Pharmaceutical Research, 2020)
Urginea indica, is an essential indigenous plant belonging to the family Liliaceae found in all parts of India on rocky and hilly areas. It is commonly known as Indian squill, True squill or Sea onion and popularly known as Bon Pollundu. A methodical literature survey from various scientific databases such as PubMed, Scopus, Web of science and Google Scholar was conducted and it has been reported that the plant, mainly its bulb contains varieties of bioactive constituents such as flavonoids, phytosterols, phenols, saponins, alkaloids, proteins, carbohydrates, steroids and tannins. The bulb and the rhizome also contains calcium, iron, commercial compounds, such as Bufadienolides, Quercetin, Allose, Mindererus spirit, Tartronic acid and Paraldehyde, which have a variety of health functional properties. Various scientific studies have proven that the plant has anticancer, antidiabetic, anthelmintic, analgesic, antibacterial, antifungal, anti-angiogenic, anti-arthritic, antioxidant, anti-inflammatory, spasmodic and cardiac stimulant activities. It also finds its use as an analgesic and in wound healing. Thus, the current review gives a comprehensive overview of the various medicinal activity of the plant Urginea indica.